Evaluation of the influence of texture and microstructure of titanium substrates on TiO2 anodic coatings at 60 V - Vera, Maria Laura (2017)
The current paper analyzes the influence of texture and microstructure of Ti substrates on morphology and color of titanium dioxide coatings obtained by anodic oxidation. Substrates of Ti grade 2 and Ti grade 5 with different thermo-mechanical histories were used in the shape of cylindrical bars cut in both longitudinal and transversal directions, and laminated sheets. The crystalline orientation of the surface grains in the substrate before oxidation, were determined by electron backscatter diffraction. The oxide coatings were analyzed by optical and scanning electron microscopy. The results show that different substrate grain orientations produce oxides with different colors, because of different thickness depending on their orientations. An oxide grown on a basal hcp plane, with higher atomic density is thinner than an oxide grown on a transversal hcp plane with lower atomic density. This effect is more pronounced on elongated grains. Different anodic oxidation process parameters and heat treatments of the substrate were applied in order to obtain a more uniform oxide thickness. A specific heat treatment of the substrate was the most efficient, starting from a favorable orientation of crystals, characteristic of rolling texture.